Effectiveness of Rural Self-Help Initiatives on Peace Building Activities in Turkana North Sub-County, Kenya - Ekidor, Paul Ekal; Okuto, Emily; Musya, Justus K. (International Journal of Conflict Management, 2025)
Purpose: The purpose of the study was to assess the effectiveness of rural self-help strategies on peace building activities in Turkana North Sub-County, Kenya. Methodology: The study used a descriptive research design. The target population was 150 respondents engaged in rural self-help initiatives in Turkana North Sub-County. The sample size was 108 selected using quota sampling. The data was collected using questionnaires and interview guides. Data collected from the field was analyzed using descriptive and inferential statistics. Descriptive statistics included frequency and percentages to analyze the measure of central tendency for each of the study variables and also the measure of diversion for each variable. Findings: The study established that Rural self-help initiatives strategies (β=0.708; p=0.000) significantly effective in enhancing peace building activities in Turkana north sub-county. The study concluded that Rural Self-Help Strategies are very effective in enhancing the peace building in Turkana North Sub-County. Unique Contribution to Theory, Policy and Practice: The study recommends that county government of Turkana through Rural self-help initiatives should engage the local community in decision-making processes. There also a need for county government of Turkana to ensure that the rural self-help initiatives implemented provide training and capacity-building programs. This would equip community members with the skills needed to take part in peacebuilding initiatives.